Don't stop me now: The impact of credit market fragmentation on firms' financing constraints - Franziska Bremus; Katja Neugebauer (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
This paper investigates how the withdrawal of banks from their cross-border business impacted the borrowing costs of European firms since the crisis. We combine aggregate information on total and cross-border credit with firm-level survey data for the period 2010 - 2014. We find that the decline in cross-border lending led to a deterioration in the borrowing conditions of small firms. In countries with more pronounced reductions in cross-border credit inflows, the likelihood of a rise in firms' external financing costs has increased. This result is mainly driven by the interbank channel, which plays a crucial role in transmitting shocks to the real sector across borders.
Keywords: F34; F36; G15; G21; 330; international banking; firm finance; credit constraints